2020
DOI: 10.33003/fjs-2020-0402-222
|View full text |Cite
|
Sign up to set email alerts
|

Manova: Power Analysis of Models of Sudoku Square Designs

Abstract: This paper assesses the performance of multivariate treatment tests (Wilk’s Lambda, Hoteling-lawley, Roy’s largest root and Pillai) on multivariate Sudoku square design models in terms of power analysis. Monte carlo simulation was conducted to compare the power of these four tests for the four multivariate Sudoku square design models. This study used  0.062 as interval value for Power difference between two tests of the same sample size. The test is considered powerful or having advantage, if the diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…This extension can provide both more precise parameter estimates and better components identification. Several researchers have presented their works on Sudoku square design, authors like, Lorch, (2009), Subramani andPonnuswamy (2009), Subramani, (2012), Ramon et al (2012), Mahdian and Mahmoodian (2015), Danbaba and Dauran (2016), Shehu and Danbaba (2018), Shehu and Danbaba (2018a) and Shehu et al (2023). This study extends the work of Shehu and Danbaba (2018), the work showed the inclusion of concomitant variable into each of the four Sudoku square models, method of least square was used to derive the estimators for sum of squares and cross products.…”
mentioning
confidence: 58%
See 3 more Smart Citations
“…This extension can provide both more precise parameter estimates and better components identification. Several researchers have presented their works on Sudoku square design, authors like, Lorch, (2009), Subramani andPonnuswamy (2009), Subramani, (2012), Ramon et al (2012), Mahdian and Mahmoodian (2015), Danbaba and Dauran (2016), Shehu and Danbaba (2018), Shehu and Danbaba (2018a) and Shehu et al (2023). This study extends the work of Shehu and Danbaba (2018), the work showed the inclusion of concomitant variable into each of the four Sudoku square models, method of least square was used to derive the estimators for sum of squares and cross products.…”
mentioning
confidence: 58%
“…Several researchers have presented their works on Sudoku square design, authors like, Lorch, (2009), Subramani andPonnuswamy (2009), Subramani, (2012), Ramon et al (2012), Mahdian and Mahmoodian (2015), Danbaba and Dauran (2016), Shehu and Danbaba (2018), Shehu and Danbaba (2018a) and Shehu et al (2023). This study extends the work of Shehu and Danbaba (2018), the work showed the inclusion of concomitant variable into each of the four Sudoku square models, method of least square was used to derive the estimators for sum of squares and cross products. The extension of the paper will be in area of analytical procedures of obtaining the least square estimates of the sums of squares and products, test of significance of the adjusted treatment effect, obtaining error mean squares for ANCOVA and ANOVA Sudoku square models, comparison of the two error mean squares and correlation coefficients between the concomitant variable and dependent variable.…”
mentioning
confidence: 58%
See 2 more Smart Citations
“…Many authors like Subramani [13], Subramani and Ponnuswamy [14], Hui-Dong and Ru-Gen [15], Dauran et al [16], Shehu and Dauran [17], Danbaba and Shehu [18], Danbaba [19], Danbaba [20], Danbaba [21] and many others. These authors have written on the areas of analysis of variance (ANOVA), construction of models, Construction of graeco Sudoku square design, multivariate analysis and variance components of Sudoku square models.…”
Section: Subramani and Ponnuswamymentioning
confidence: 99%